2017
DOI: 10.3390/en10030273
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of BMSs on the Characterization and Modeling of Series and Parallel Li-Ion Packs

Abstract: This work analyzes the effects of a BMS (battery management system) on the characterization and modeling of series and parallel connections of Li-ion cell packs. The Li-ion pack studied consists of four series modules connected in parallel. This pack has been characterized by means of charge, discharge and frequency tests. As a result of these tests, series and parallel influence on battery parameters have been determined. A model considering the effects of a BMS is established and compared with a model based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Böylece empedans verilerinin yorumlanabilmesinin önü de açılmıştır. Ayrıca, modele dayalı empedans analizi ile farklı pil koşullarında batarya performansının ve pil kapasitesinin azalmasına neden olan mekanizmaların daha iyi anlaşılması amaçlanmaktadır [13,18,19]. Bununla birlikte bir eşdeğer devre modelinin tanımlanması şarj/deşarj süreçleri boyunca bataryada meydana gelen fiziksel olayları anlamak ve fayda durumunu değerlendirmek için kullanılacak yöntemlerin belirlenmesi için de önem taşımaktadır [21].…”
Section: Gi̇ri̇ş (Introduction)unclassified
See 1 more Smart Citation
“…Böylece empedans verilerinin yorumlanabilmesinin önü de açılmıştır. Ayrıca, modele dayalı empedans analizi ile farklı pil koşullarında batarya performansının ve pil kapasitesinin azalmasına neden olan mekanizmaların daha iyi anlaşılması amaçlanmaktadır [13,18,19]. Bununla birlikte bir eşdeğer devre modelinin tanımlanması şarj/deşarj süreçleri boyunca bataryada meydana gelen fiziksel olayları anlamak ve fayda durumunu değerlendirmek için kullanılacak yöntemlerin belirlenmesi için de önem taşımaktadır [21].…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Elektromanyetik etkilerden kaynaklanan indüktans (L) ise kHz ve daha yüksek frekanslarda gözlemlenebilmektedir [5]. Ancak, çoğu elektriksel uygulamanın yüksek frekansta gerçekleşmiyor olmasından dolayı indüktif davranış ihmal edilebilmektedir [18]. Böylece çeşitli frekanslarda pil ve pil sistemlerinin oluşturduğu batarya paketlerinde meydana gelen prosesler hakkında bilgi edinilebilmektedir.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Li-ion battery-packs are modeled in the majority of the cases as an aggregation of individual cell models, neglecting the packaging effects of multicell devices, although some recent works have shown that considering the interactions between cells and BMS elements can improve the accuracy of the Li-ion battery-packs models [22,23]. Also, most battery models do not consider that battery modules can work at different dynamic regimes due to internal electrochemical processes that affect their transient behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These frequency regions of the Nyquist plot provide information for ohmic resistance at high frequencies, charge transfer resistance and double layer capacitance at midfrequencies, diffusion of the ions through electrolyte/electrode interphase at low frequencies (Itagaki, Honda, Hoshi, & Shitanda, 2015). To obtain battery parameters, a model that simulates characteristics of a battery was applied to the EIS data (Castano-Solis, Serrano-Jimenez, Gauchia, & Sanz, 2017). The battery models are designed as an equivalent circuit consisting of various kinds of elements such as electrolyte resistances, capacitances, inductances, charge transfer resistances, constant phase elements, Warburg elements, and so on.…”
Section: Introductionmentioning
confidence: 99%